X‐ray‐induced degradation of OEG‐terminated SAMs on silica surfaces during XPS characterization. (17th April 2015) - Palazon, Francisco; Géhin, Thomas; Ferrah, Djawhar; Garnier, Anaïs; Botella, Claude; Grenet, Geneviève; Souteyrand, Éliane; Cloarec, Jean‐Pierre; Chevolot, Yann
<x xml:space="preserve">Abstract</x> Oligo ethylene glycol layers are widely used in biosensor applications, mainly for their anti‐fouling abilities. Such surfaces are often characterized by X‐ray photoelectron spectroscopy (XPS) as this method allows a precise determination of the surface chemical composition. We show herein that X‐rays used during XPS characterization quickly and significantly degrade oligo ethylene glycol immobilized onto silica substrates. It is therefore necessary to introduce a correcting factor to assess the true (i.e. without degradation) corresponding ether contribution in the XPS spectrum of such organic layers. Eventually, fluorescence scans show the loss of anti‐fouling properties of the degraded surface, leading to greater amounts of adsorbed (fluorescently labeled) protein. Copyright © 2015 John Wiley & Sons, Ltd.